Distribution and Viability of Fetal and Adult Human Bone Marrow Stromal Cells in a Biaxial Rotating Vessel Bioreactor after Seeding on Polymeric 3D Additive Manufactured Scaffolds - Leferink, Anne M.; Chng, Yhee-Cheng; van Blitterswijk, Clemens A.; Moroni, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2015)
One of the conventional approaches in tissue engineering is the use of scaffolds in combination with cells to obtain mechanically stable tissue constructs in vitro prior to implantation. Additive manufacturing by fused deposition modeling is a widely used technique to produce porous scaffolds with defined pore network, geometry, and therewith defined mechanical properties. Bone marrow derived mesenchymal stromal cells (MSCs) are promising candidates for tissue engineering based cell therapies due to their multipotent character. One of the hurdles to overcome when combining additive manufactured scaffolds with MSCs is the resulting heterogeneous cell distribution and limited cell proliferation capacity. In this study, we show that the use of a biaxial rotating bioreactor, after static culture of human fetal MSCs (hfMSCs) seeded on synthetic polymeric scaffolds, improved the homogeneity of cell and extracellular matrix (ECM) distribution and increased the total cell number. Furthermore, we show that the relative mRNA expression levels of indicators for stemness and differentiation are not significantly changed upon this bioreactor culture, whereas static culture shows variations of several indicators for stemness and differentiation. The biaxial rotating bioreactor presented here offers a homogeneous distribution of hfMSCs, enabling studies on MSCs fate in additive manufactured scaffolds without inducing undesired differentiation.